Do You Love to see the circus?

Algebra Level pending

A circus party has same number of L i o n s Lions as T i g e r s . Tigers. You asked to the owner of the circus the number of l i o n s lions and t i g e r s . tigers. The owner was a very funny person and he gave you the following information :

( i ) (i) A n An e l e p h a n t elephant is enough to feed all the t i g e r s tigers and l i o n s lions in the circus.

( i i ) (ii) 18 18 deer produce the same amount of meat as a n an e l e p h a n t elephant does.

( i i i ) (iii) A L i o n Lion eats t w i c e twice as a T i g e r Tiger .

( i v ) (iv) 1 1 b u f f a l o buffalo is enough to feed a L i o n Lion and a T i g e r Tiger .

( v ) (v) A T i g e r Tiger will eat exactly the same amount of meat a d e e r deer has.

Find the number of T i g e r s Tigers and L i o n s Lions in that circus party.


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Abdullah Ahmed
Jun 28, 2016

Let the number of tigers (and lions) be x x

1 1 All of 2 x 2x animals eat in total 3 x 3x (a single tiger's food)

2 2 3 x 3x (a single tiger's food) = an elephant.

3 3 3 x 3x (a single tiger's food) = 18 18 deer .

4 4 3 x 3x (a single tiger's food) = 18(a single tiger's food)

So, 3 x 3x = 18 18

x x = 6 6 .

Hung Woei Neoh
Jul 1, 2016

Let number of lions = number of tigers = x x

Let the amount a lion eats be a a and the amount a tiger eats be b b

Let the amount of meat an elephant has be e e , and the amount of meat a deer has be d d

From the information given:

  1. e = a x + b x e=ax+bx
  2. e = 18 d e=18d
  3. a = 2 b a=2b
  4. Irrelevant information
  5. b = d b=d

Substitute (2) into (1):

18 d = a x + b x 18d=ax+bx\implies (6)

Next, substitute (3) into (6):

18 d = ( 2 b ) x + b x 18 d = 3 b x 18d=(2b)x+bx \implies 18d=3bx\implies (7)

After that, substitute (5) into (7):

18 d = 3 d x x = 18 d 3 d = 6 18d=3dx \implies x=\dfrac{18d}{3d} = \boxed{6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...